Extensive characterisation of a high Reynolds number decelerating boundary layer using advanced optical metrology. Issue 10 (3rd October 2017) - Cuvier, C.; Srinath, S.; Stanislas, M.; Foucaut, J. M.; Laval, J. P.; Kähler, C. J.; Hain, R.; Scharnowski, S.; Schröder, A.; Geisler, R.; Agocs, J.; Röse, A.; et al.
ABSTRACT: Over the last years, the observation of large-scale structures in turbulent boundary layer flows has stimulated intense experimental and numerical investigations. Nevertheless, partly due to the lack of comprehensive experimental data at sufficiently high Reynolds number, our understanding of turbulence near walls, especially in decelerating situations, is still quite limited. The aim of the present contribution is to combine the equipment and skills of several teams to perform a detailed characterisation of a large-scale turbulent boundary layer under adverse pressure gradient. Extensive particle image velocimetry (PIV) measurements are performed, including a set-up with 16 sCMOS cameras allowing the characterisation of the boundary layer on 3.5 m, stereo PIV and high resolution near wall measurements. In this paper, detailed statistics are presented and discussed, boundary conditions are carefully characterised, making this experiment a challenging test case for numerical simulation.